Linguistic and Psychometric Validation of the Ukrainian Translation of the Inventory of Personality Organization-Revised (IPO-R-UKR) - Semkiv, Iryna; Turetska, Khrystyna; Kryvenko, Iryna; Kechur , Roman (East European Journal of Psycholinguistics, 2022)
The cultural adaptation of the psychodiagnostic questionnaire involves the implementation of a “double-blind” translation with subsequent linguistic validation considering both linguistic differences and the symbolism of the authors’ statements. Then, based on the survey data of respondents, various psychometric indicators of the questionnaire are checked. The development of Ukrainian-language questionnaires in the psychodynamic paradigm is crucial for creating an appropriate scientific evidence base of therapeutic methods and for psychotherapeutic practice to equip specialists with reliable diagnostic tools. The research objective is to carry out a professional translation of The Inventory of Personality Organization-Revised (IPO-R) into Ukrainian, followed by checking for linguistic validity and psychometric properties. The questionnaire showed high psychometric performance in the long (IPO; Lenzenweger et al., 2001) and short (IPO-R; Smits et al., 2009) versions and foreign language adaptations. It is widely used in psychological research, the theoretical and methodological basis of which is the psychoanalytic concept, in particular, the theory of Kernberg (1986) on different levels of structural organization of personality, which underlies the psychoanalyst's choice of a strategy for working with a client. The created test version of the IPO-R-UKR questionnaire passed the stages of two-sided "double-blind" translation and was agreed upon by a team of philologists and psychologists. Based on the results of 1152 people participating in the empirical research, we have proven IPO-R-UKR to have a similar to the original two-factor structure, good internal consistency of the scales, construct convergent, and criterion validity. Thus, IPO-R-UKR can be used in practical psychological activities and scientific research to identify criteria for the structural organization of personality, such as reality testing, identity diffusion, and mechanisms of psychological defenses, as well as for screening diagnostics of the structural level of personality organization by Kernberg (1986).
Keywords: linguistic validity, Ukrainian translation, structural personality organization, identity diffusion, reality testing, defense mechanisms, psychodynamic therapy